Perancangan dan Implementasi Aplikasi Web Promosi Kos Graha - Syaifuddin Luqman Hakim; Eko Hariyanto; Arpan (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
The development of information technology is driving the transformation of promotional strategies in various fields, including the residential rental sector such as boarding houses. The purpose of this study is to design and build a web application that functions as a promotional medium for Kos Graha to expand its marketing reach and facilitate access to information for prospective tenants. The approach used is descriptive qualitative, with data collection techniques through field observations, structured interviews, and documentation studies. The system design was carried out based on user needs analysis, followed by the development of an HTML, CSS, JavaScript, and PHP-based interface, and database management using MySQL. The implementation results show that the application is able to present boarding house information comprehensively, attractively, and easily accessible, and supports features such as photo galleries, facility descriptions, booking forms, and location map integration. Testing with five users showed a high level of satisfaction with the application's appearance and ease of navigation. Promotional reach increased significantly, as evidenced by the increasing number of prospective tenants who learned about the boarding house through the application and the increase in sales. This application also successfully overcomes the barriers of conventional promotions that are limited geographically and informationally. In conclusion, this web application is effective in expanding the promotional reach of Kos Graha while increasing communication efficiency and information access for prospective tenants.